Algebra and computer science - Joint AMS-EMS-SPM Meeting on Algebra and Computer Science (Porto, Portugal 10-13 June 2015); Kahrobaei, Delaram; Cavallo, Bren; Garber, David; Joint Mathematics Meetings on Groups, Algorithms, and Cryptography (San Antonio, TX 10-13 Jan 2015); Joint AMS-Israel Mathematical Union Meeting on Applications of Algebra to Cryptography (Tel Aviv, Israel 16-19 June 2014) (Providence : American Mathematical Society, 2016)
This volume contains the proceedings of three special sessions: Algebra and Computer Science, held during the Joint AMS-EMS-SPM meeting in Porto, Portugal, June 10-13, 2015; Groups, Algorithms, and Cryptography, held during the Joint Mathematics Meeting in San Antonio, TX, January 10-13, 2015; and Applications of Algebra to Cryptography, held during the Joint AMS-Israel Mathematical Union meeting in Tel-Aviv, Israel, June 16-19, 2014. Papers contained in this volume address a wide range of topics, from theoretical aspects of algebra, namely group theory, universal algebra and related areas, to applications in several different areas of computer science. From the computational side, the book aims to reflect the rapidly emerging area of algorithmic problems in algebra, their computational complexity and applications, including information security, constraint satisfaction problems, and decision theory. The book gives special attention to recent advances in quantum computing that highlight the need for a variety of new intractability assumptions and have resulted in a new area called group-based cryptography.
* F. Bassino, C. Nicaud, and P. Weil, Generic properties of subgroups of free groups and finite presentations* C. S. Chum and X. Zhang, A new multi-server scheme for private information retrieval* C. S. Chum, B. Fine, A. I. S. Moldenhauer, G. Rosenberger, and X. Zhang, On secret sharing protocols* M. E. Habeeb, A verifiable secret sharing scheme using non-abelian groups* A. Kalka, Non-associative public-key cryptography* A. Kalka and M. Teicher, Non-associative key establishment protocols and their implementation* D. Konig, M. Lohrey, and G. Zetzsche, Knapsack and subset sum problems in nilpotent, polycyclic, and co-context-free groups* I. S. Moldenhauer, G. Rosenberger, and K. Rosenthal, On the Tits alternative for a class of finitely presented groups with a special focus on symbolic computations* A. Sale, Geometry of the conjugacy problem in lamplighter groups* A. Weiss, A logspace solution to the word and conjugacy problem of generalized Baumslag-Solitar groups* S. Yuan, Cryptographic hash functions from sequences of lifted Paley graphs.
Includes bibliographical references.
Keywords: Symbolic and mathematical logic -- Congresses; Algebra -- Congresses; Computer science -- Mathematics -- Congresses